2015
DOI: 10.1536/ihj.14-396
|View full text |Cite
|
Sign up to set email alerts
|

Can Pulmonary Vasodilator Therapy Expand the Operative Indications for Congenital Heart Disease?

Abstract: SummaryThe operability of congenital heart disease with left to right shunt depends on the severity of the pulmonary vascular disease induced by the increased pulmonary blood flow. Although some recommendations exist regarding operative indications according to pathological, hemodynamic, and epidemiological factors, the evidence underlying these recommendations is not conclusive. Recently, oral pulmonary vasodilator therapy has been reported to improve outcomes in patients with idiopathic pulmonary arterial hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…[28] The limited exercise tolerance and exertional dyspnea could remain persistent for years, which identify a risk for hospitalization, severe cardiovascular events, or death point. Inai [29] concluded that pulmonary vasodilators are probably available to interfere with the ongoing disease process to improve functional capacity and delay the decision for transplantation with no conclusive evidence. Although retrospective studies suggested ES patients with PAH-SDT benefitted from a longer lifespan, improved hemodynamics lasting period for operation, no recommendations for patients with ES have existed.…”
Section: Discussionmentioning
confidence: 99%
“…[28] The limited exercise tolerance and exertional dyspnea could remain persistent for years, which identify a risk for hospitalization, severe cardiovascular events, or death point. Inai [29] concluded that pulmonary vasodilators are probably available to interfere with the ongoing disease process to improve functional capacity and delay the decision for transplantation with no conclusive evidence. Although retrospective studies suggested ES patients with PAH-SDT benefitted from a longer lifespan, improved hemodynamics lasting period for operation, no recommendations for patients with ES have existed.…”
Section: Discussionmentioning
confidence: 99%
“…2-4) Recently, the survival of newborns with CHDs has increased due to massive breakthroughs in cardiovascular diagnostics and cardiothoracic surgery, 5,6) however, this trend consequently generates a completely novel and steady increasing population with grown-up congenital heart disease (GUCH). Patients with GUCH often need long-term expert medical care with high healthcare-related costs.…”
Section: Discussionmentioning
confidence: 99%
“…CHD is the most common type of congenital deformity, classified into three types based on hemodynamics: no shunt, left to right shunt, and right to left shunt. [405][406][407] Patients with cyanotic CHD (CCHD) might have a hypoxic response, which leads to abnormalities in endothelial function, vascular remodeling, and thrombosis after emergency surgery. 408 Prolyl-4-hydroxylase2 (PHDP2)/HIF-1α pathway is the key regulator under hypoxia.…”
Section: Hypoxia In Arrhythmiamentioning
confidence: 99%